Diversity of Fusarium species isolated from soil cultivated with cucurbits within East Coast, Peninsular Malaysia - Mohamed Sidique, Siti Nordahliawate; Mohd Zainuddin, Nur Ain Izzati; Azhari, Nur Azlin; Salleh, Baharuddin (Universiti Putra Malaysia Press, 2012)
Fungi in the genus Fusarium are well known as soil-borne pathogen with worldwide distribution. Therefore, this study focused on isolation of Fusarium species from soil cultivated with watermelons, muskmelon, pumpkins, and cucumber in the east coast of Peninsular Malaysia by using dilution plate technique, direct plating and debris plating. The highest number of Fusarium species isolated was F. oxysporum with 687 (26.2%) colonies counted based on colony formation unit (CFU); the colonies of Fusarium/g soil = mean of Fusarium colonies x dilution factor/weight of dried soil (g). Other Fusarium species isolated were F. semitectum, F. solani, F. proliferatum, F. subglutinans and F. chlamydosporum. Throughout the studies, peptone pentachloronitrobenzene (PPA) medium, potato dextrose agar (PDA) and carnation leaf-piece agar (CLA) were regularly used to identify each Fusarium species by morphological means. Based on the Shannon-Weiner Index, Fusarium species diversity is much higher in Besut, Terengganu (H’=1.59). Fusarium species can be considered as a functionally important biological component of Fusarium fruit rot disease study in cucurbits.